Strategi Pemasaran Untuk Upaya Meningkatkan Jumlah Nasabah Pada Produk Pembiayaan KPR Di PT Bank Tabungan Negara Kantor Cabang Cilegon - Fajar Nugraha Permana; Asmai Ishak (Pusat Riset dan Inovasi Nasional, 2023)
The banking world, experienced a very rapid development. That way, competition between banking products is inevitable and increasingly fierce. One of them is the Home Ownership Credit (KPR) product. Banks must have an effective and efficient marketing strategy, so as to support the company's operational activities to dominate market segments, and also have the attractiveness to market mortgage products in order to attract consumers and compete with other banks. This study aims to determine the application of tactics and marketing strategies of Bank Tabungan Negara Cilegon Branch Office in increasing the number of customers in mortgage financing products. The methodology used in this study uses a qualitative approach, namely by conducting literature research, which is a data collection technique using written sources. Field research, namely techniques with data collection by observation methods, interviews with employees of the Marketing Department of Bank Tabungan Negara Cilegon Branch Office who are responsible for marketing mortgage products so as to obtain accurate data in the research process studied. Through interviews and observations, it can be seen that the marketing strategy carried out by Bank Tabungan Negara Cilegon Branch Office in marketing Home Ownership Credit (KPR) products is to use Segmenting, Targeting, Positioning (STP) and also Marketing Mix 3P (Product, Price, Promotion).